Material insecurity predicts greater commitment to moralistic and less commitment to local deities: a cross-cultural investigation - Baimel, A; Apicella, CL; Atkinson, Q; Cohen, E (Routledge, 2022)
The existential security hypothesis predicts that in the absence of more successful secular institutions, people will be attracted to religion when they are materially insecure. Most assessments, however, employ data sampled at a state-level with a focus on world religions. Using individual-level data collected in societies of varied community sizes with diverse religious traditions including animism, shamanism, polytheism, and monotheism, we conducted a systematic cross-cultural test (N = 1820; 14 societies) of the relationship between material insecurity (indexed by food insecurity) and religious commitment (indexed by both beliefs and practices). Moreover, we examined the relationship between material security and individuals’ commitment to two types of deities (moralistic and local), thus providing the first simultaneous test of the existential security hypothesis across co-existing traditions. Our results indicate that while material insecurity is associated with greater commitment to moralistic deities, it predicts less commitment to local deity traditions.